Concepções escatológicas na religiosidade nórdica pré- cristã e cristã: Um estudo comparativo - Oliveira, Angela Albuquerque de (2017)
This work aims to analyze the Ragnarök myth with regard to possible Christian influences present in its composition in the Scandinavian Viking Age, considering the context of the tenth century A.D. The theoretical-methodological approach that leads this study is based on the perspective of the Cultural History of Religions. It scrutinizes the referred myth, which is part of the pre-Christian cycle of beliefs (eighth to eleventh centuries). Such cycle concerns a future cosmic catastrophe, predicting the end of a cosmic cycle and the decease of some gods. It is evident, thus, that this work contributes both to the Postgraduate Program of Religious Studies from the Federal University of Paraíba (UFPB) and to the broad field of Religious Studies. Its approach is characterized by the qualitative research, specifically the comparative study. The contextual comparison between the pre-Christian and Christian Norse religiosity will be performed through content analysis, along with the technical procedure adopted for the bibliographical research that is descriptive and systematizes the themes involved. Concepts from Cultural History and the Italian School of History of Religions will be used not only as theoretical support but also as a proposal for researches in Medieval Scandinavian Studies. The pre-Christian Norse religiosity, composed by an oral tradition and written down after the christianization (thirteenth century), underwent constant influences caused by interactions with the continent and the tension between these traditions and the Christian-influenced ones. The comparison of images and symbols found in crosses that were used for the evangelization of a practically illiterate people has provided a mapping of ideas and motifs concerning Christian reminiscences present in such monuments. In those it was possible to inquire how deep the historical antecedents of a christianization affected the corpus of the myth Ragnarök, in which it possibly announces the victory of the Christian faith and the fall of the Norse gods. An example of such context regards the confluence of PreChristian and Christian religious motifs, identified in mortuary monuments localized in some regions of the British Isles, where vikings have settled. Therefore, it is postulated that this eschatological conception: 1) resulted from the meeting of elements raised in different contexts, in a way that they had directly absorbed symbols, images, and textual traditions which provided reminiscent Christian ideas and motifs for the native material; and 2) was rebuilt in a particular context of the pre-Christian Norse religiosity, influencing the composition of the poem Völuspá, but also with the clear intention of the poet to conserve such myths.